1994
DOI: 10.1203/00006450-199404000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Echocardiographic Evaluation of Left Ventricular Output and Left Ventricular Diastolic Filling Changes in the First Day of Life

Abstract: MATERIALS AND METHODSThe loading condition of the left ventricle changes markedly during the transition from fetal to neonatal circulation and continues to be unstable shortly after birth. During this period, pulmonary blood flow, which acts as preload to the left ventricle, increases because of left-to-right ductus arteriosus shunting (I, 2). Among the hemodynamic factors affecting left ventricular diastolic filling, preload appears to play an important role, as has been recently suggested (3,4). Interest ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 28 publications
3
17
1
1
Order By: Relevance
“…Similar to the other Doppler studies (Drayton and Skidmore 1987; Agata et al 1991), we previously demonstrated that the left-to-right ductal shunt increased at 2 hr of age and decreased rapidly by 12 hr of age (Harada et al 1994). In the present study, the left atrial to aortic root ratio and the inner diameter of the ductus arteriosus significantly increased in group 1 (mean age 1.8 hr after birth) compared with group 2 (mean age =13.0 hr after birth), thus the LV preload was suggested to be higher in group 1 than group 2.…”
Section: Discussiqnsupporting
confidence: 90%
“…Similar to the other Doppler studies (Drayton and Skidmore 1987; Agata et al 1991), we previously demonstrated that the left-to-right ductal shunt increased at 2 hr of age and decreased rapidly by 12 hr of age (Harada et al 1994). In the present study, the left atrial to aortic root ratio and the inner diameter of the ductus arteriosus significantly increased in group 1 (mean age 1.8 hr after birth) compared with group 2 (mean age =13.0 hr after birth), thus the LV preload was suggested to be higher in group 1 than group 2.…”
Section: Discussiqnsupporting
confidence: 90%
“…Among the hemodynamic factors affecting left and right ventricular diastolic filling, preload appears to play an important role, as documented by recent studies (Choong et al 1987; Courtois et al 1988; Triulzi et al 1990; Odake et al 1991;Castini et al 1992). We have demonstrated the effects of a patent ductus arteriosus on left ventricular diastolic filling (Harada et al 1994) However, the impact of changes in preload on the transtricuspid flow pattern in this period is less clear. The purpose of our present study was to evaluate the serial changes of right ventricular filling patterns in normal neonates during their transition to postnatal circulation.…”
mentioning
confidence: 62%
“…Choong et al (1987) reported that nitroglycerin altered the Doppler characteristics of the early filling wave. We have previously demonstrated the effects of ductus arteriosus on the left ventricular diastolic filling (Harada et al 1994), however, little attention has been paid to right ventricular diastolic filling in the early neonatal period. To our knowledge, this is the first serial evaluation of the relation between right ventricular output changes and right ventricular diastolic filling changes in normal human subjects during the early neonatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Transmitral VTI can be measured to give an estimate of flow across the atrioventricular valves. 21 The Tei index (or myocardial performance index) has been found to be a valuable quantitative echocardiography index of ventricular function by incorporating both systolic and diastolic performance of the right and left ventricles (Fig.-4). It is defined as the sum of isovolumetric contraction and relaxation times divided by the ejection time, which requires measurement of the time interval between the end and onset of mitral or tricuspid inflow (the 'a' interval) and the ejection time of the LV or RV outflow (the 'b' interval).…”
Section: Diastolic Performancementioning
confidence: 99%